2010
DOI: 10.5507/bp.2010.051
|View full text |Cite
|
Sign up to set email alerts
|

Mallampati Test as a Predictor of Laryngoscopic View

Abstract: Aim.To determine the accuracy of the modified Mallampati test for predicting difficult tracheal intubation. Design. A cross-sectional, clinical, observational, non-blinded study. A quality analysis of anesthetic care. Setting. Operating theatres and department of anesthesiology in a university hospital. Material and methods. Following the local ethics committee approval and patients' informed consent to anesthesia, all adult patients (> 18 yrs) presenting for any type of non-emergency surgical procedures under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
2
41
0
9
Order By: Relevance
“…In the literature, class 3 means up to 7.5-8 times higher risk for difficult intubation. But a 1992 German study showed that only 6.4% of class 4 patients were difficult to intubate 3,5 . Although ULBT is a statistically significant test, in some cases such as elderly patients with artificial dentition, it may be more difficult to understand and perform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, class 3 means up to 7.5-8 times higher risk for difficult intubation. But a 1992 German study showed that only 6.4% of class 4 patients were difficult to intubate 3,5 . Although ULBT is a statistically significant test, in some cases such as elderly patients with artificial dentition, it may be more difficult to understand and perform.…”
Section: Discussionmentioning
confidence: 99%
“…The actual predictive value is approximately 50% (ref. 3,5 ). In the literature, class 3 means up to 7.5-8 times higher risk for difficult intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most notable and frequently used clinical signs are the extent of neck mobility, the Mallampati score, the McCormack and Lehane score, and the thyromental distance. The Mallampati score is a numerical score ranging from 1 to 4 given to a patient based on visualization of intraoral anatomical landmarks when a patient opens his/her mouth; with a score of 1 signifying visualization of fauces, pillars, soft palate, and uvula; score of 2 given upon visualization of fauces, soft palate, and uvula; score of 3 given upon visualization of soft palate and base of uvula; and a score of 4 signifying visualization of only the hard palate [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The Cormack and Lehane Classification system grades visualization of an airway during direct laryngoscopy into 4 grades, with grade 1 providing a full view of the glottis including the airway, grade 2 giving a patial glottis view, grade 3 affording a view only of the epiglottis, and grade 4 furnishing only a view of the soft palate without epiglottis visualization [4,5].…”
Section: Discussionmentioning
confidence: 99%